2013
DOI: 10.1038/jcbfm.2013.118
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Reduction of Edema with Aquaporin-4 RNA Interference Improves Acute and Chronic Functional Recovery

Abstract: Traumatic brain injury (TBI) is common in young children and adolescents and is associated with long-term disability and mortality. The neuropathologic sequelae that result from juvenile TBI are a complex cascade of events that include edema formation and brain swelling. Brain aquaporin-4 (AQP4) has a key role in edema formation. Thus, development of novel treatments targeting AQP4 to reduce edema could lessen the neuropathologic sequelae. We hypothesized that inhibiting AQP4 expression by injection of small-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(124 citation statements)
references
References 40 publications
7
116
0
1
Order By: Relevance
“…Others support the idea that AQP4 expression increases following similar insults and may provide a key avenue for strategies aimed at reducing its effects. [57][58][59] On the other hand, a decrease in AQP4 expression was reported using a CCI model at more chronic time points 60 but these authors concluded 1264 FILIPPIDIS ET AL.…”
Section: Beneficial Effects Of V1ar Inhibition By Sr49059mentioning
confidence: 85%
“…Others support the idea that AQP4 expression increases following similar insults and may provide a key avenue for strategies aimed at reducing its effects. [57][58][59] On the other hand, a decrease in AQP4 expression was reported using a CCI model at more chronic time points 60 but these authors concluded 1264 FILIPPIDIS ET AL.…”
Section: Beneficial Effects Of V1ar Inhibition By Sr49059mentioning
confidence: 85%
“…21 All tests at each time-point were carried out on WT and AQP4 À/À mice within a 3-h morning time-block (8-11 am) and WT and AQP4 À/À were interleaved during the testing sequence. Foot-fault testing was carried out on an elevated platform (50 cm  155 cm, ClosetMaid, Ocala, FL, USA) with parallel wire bars 1.5 cm apart and raised 100 cm above the floor.…”
Section: Behavioral Testingmentioning
confidence: 99%
“…The tissue section with the largest lesion was selected and the NeuN positive cells were counted in an automated fashion via the Mercator software and the density was determined. 21 Statistics MRI and behavioral data were analyzed by two-way repeated measures analysis of variance with a post hoc Bonferroni test. One-way ANOVA was used for immunohistochemistry analysis.…”
Section: Tissue Processing and Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Within 10 min after unilateral controlled cortical impact (CCI), immature (P17) male rats were injected intracortically with siAQP4 adjacent to the site of the impact. 37,38 A second siRNA injection was repeated 2 days later, to maintain the decrease of AQP4 expression. 23 Based on previous monotherapy studies with D-JNKI-1 in juvenile animals, 35 11 mg/kg was administered IP at 3 h postinjury.…”
Section: Concurrent Targeted Therapy Combination: Aqp4 and Jnk Inhibimentioning
confidence: 99%